2020
DOI: 10.18632/oncotarget.27323
|View full text |Cite
|
Sign up to set email alerts
|

Response of a chemo-resistant triple-negative breast cancer patient to a combination of p62-encoding plasmid, Elenagen, and CMF chemotherapy

Abstract: Triple-negative breast cancers are often characterized by aggressive behavior and short clinical course once they become chemotherapy-resistant. We describe below a patient who has shown a response to combination of chemotherapy with Elenagen, a plasmid encoding p62. Elenagen was tested in a previous phase I/II study in patients with refractory solid tumors and shown to be safe. Also, plasmid ability to halt tumor progression and restore sensitivity to chemotherapy was found. Preclinical data supports effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Intriguingly, a p62 encoding plasmid named Elenagen was used in association with standard chemotherapy to treat a chemoresistant triple-negative breast cancer patient with significant improvement in the response and increase in progression-free survival [ 90 ].…”
Section: Oncojanus Role Of P62mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a p62 encoding plasmid named Elenagen was used in association with standard chemotherapy to treat a chemoresistant triple-negative breast cancer patient with significant improvement in the response and increase in progression-free survival [ 90 ].…”
Section: Oncojanus Role Of P62mentioning
confidence: 99%
“…In this regard, Liu et al showed that low nuclear level of p62 was associated with aggressive clinic pathologic features and unfavourable prognosis of oral squamous cell carcinoma [89]. Intriguingly, a p62 encoding plasmid named Elenagen was used in association with standard chemotherapy to treat a chemoresistant triple-negative breast cancer patient with significant improvement in the response and increase in progression-free survival [90].…”
Section: Antitumor Role Of P62mentioning
confidence: 99%
“…Among the breast cancer subtypes, triple-negative breast cancer (TNBC) is characterized by the absence of estrogen and progesterone receptors and lack of excess of human epidermal growth factor receptor 2 (HER2) expression. TNBC accounts for about 15% of all breast cancer cases ( 2 ), and TNBC cells exhibit low levels of differentiation as well as rapid and aggressive proliferation ( 3 ). A number of cancer features in TNBC cells have been reported to depend on Ca 2+ influx across the plasma membrane.…”
mentioning
confidence: 99%
“…Accordingly, the same team reported the case of a heavily-pretreated, chemo-resistant TNBC patient treated with the combination of weekly Elenagen and cyclophosphamide/methotrexate/fluorouracil (CMF) chemotherapy. The patient experienced a 33% partial tumor regression and 19 weeks of PFS [ 65 ]. Considering these positive results, further studies of such combinations on larger TNBC patient populations are eagerly awaited.…”
Section: Resultsmentioning
confidence: 99%